Physical activity and motivation in physical therapy students at the University of Pamplona (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2013)
Objective: To establish a correlation between the level and motivation toward physical activity in physical therapy students at the University of Pamplona during the second semester of 2009. Methodology: Descriptive cross-sectional study with a population of 134 students selected by simple random sampling, who were given the abbreviated version of the International Physical Activity Questionnaire (IPAQ) and the Revised Physical Activity Motivation Scale (MPAM-R). Results The mean Physical Activity Index (PAI) was 2339.6 mets/min/week (SD: 3048.5). According to the Physical Activity Level (PAL), 48 of the subjects were classified as low level (35.8%), 30 as medium level (22.4%), and 56 as high level (41.8%). Regarding the five categories of motivation for physical activity, participants ranked enjoyment as their top priority (57.5%), followed by fitness (41%), appearance (9.7%), competition (4.5%), and social (0.7%). Conclusions Although the figures found for compliance with the minimum PA recommendation (64.2%) are satisfactory compared to studies showing high values of students who do not meet the minimum recommendation, there is a percentage of students (35.8%) in the sample who have low levels of PA. From the point of view of motivation towards physical activity, finding enjoyment as the first priority and fitness as the second is consistent with other studies which show that health and fun-related motives are those with the highest values. Based on self-determination theory, the findings show greater motivation among students within the self-determined profile, which is related to intrinsic motivation.